Dietary Glycemic Index and Glycemic Load and the Risk of Prostate Cancer: An Updated Systematic Review and Dose–Response Meta-Analysis. (2nd January 2020) - Sadeghi, Alireza; Sadeghi, Omid; Khodadost, Mahmoud; Pirouzi, Aliyar; Hosseini, Banafsheh; Saedisomeolia, Ahmad
Abstract: A meta-analysis in 2015 revealed no significant association between glycemic index (GI), glycemic load (GL), and prostate cancer. Moreover, until now, no study has examined the dose–response association of GI, GL, and prostate cancer yet. The online databases were searched by two independent researchers for relevant publications up to Jan. 2019, using relevant keywords. Nine studies including five prospective and four case–control studies were included in the current systematic review and meta-analysis. These studies have included 290, 911 individuals. We found a significant positive dose–response association between dietary GI and prostate cancer ( P nonlinearity = 0.03). Comparing individuals in the highest category of GI with those in the lowest category, no significant association was found between GI and prostate cancer (combined effect size: 1.08, 95% CI: 0.97–1.19, P =  0.17). Furthermore, no significant association was seen between dietary GL and prostate cancer in both dose–response analysis and when comparing the highest versus lowest categories of GL (combined effect size: 1.03, 95% CI: 0.91–1.16, P =  0.65). In conclusion, we found a significant positive dose–response association between dietary GI and prostate cancer. However, significant association was not seen for dietary GL.